Charting developmental trajectories from 12 to 36 months and associated early risk and protective factors. Issue 2 (June 2023) - Roe, Elizabeth; Jensen, Lynn; Finlay-Jones, Amy; White, Scott W; Wong, Kingsley; Leonard, Helen; Straker, Leon; Downs, Jenny
Aim: To investigate developmental trajectories in early childhood and predictors of class assignment. Methods: Data were available for Gen2 infants at 12 ( n = 2275), 24 ( n = 1845) and 36 ( n = 2110) months of age in the Raine Study. Latent growth class analysis was used to identify developmental trajectories based on the Ages and Stages Questionnaire. Multivariate logistic regression analyses were used to estimate associations between foetal growth restriction, gestational age, child biological sex, breast feeding, parental age, socioeconomic factors and developmental trajectories. Results: Two groups of infants were identified, one typically performing and one poorer performing. Being born early-term, pre-term and male were associated with poorer development. Not exposed to breastfeeding was associated with the lower trajectories in the adaptive and personal-social domains. Conclusions: Developmental surveillance and advice for early-term infants should be considered. Findings highlight the continued need to support and promote breastfeeding as a protective mechanism for child development.